Thermosensitive gallic acid-conjugated hexanoyl glycol chitosan as a novel wound healing biomaterial. (15th May 2021) - Park, Seul Gi; Li, Mei-Xian; Cho, Woo Kyung; Joung, Yoon Ki; Huh, Kang Moo
Highlights: Gallic acid−conjugated hexanoyl glycol chitosan (GA-HGC) was developed as a novel wound healing biomaterial. GA-HGCs exhibit thermogelation, self-crosslinkability, and self-healing ability. GA-HGC hydrogels show strong tissue adhesive strength and high compressive strength. GA-HGC hydrogel promotes wound closure and tissue regeneration. Abstract: In the present study, a novel synthetic tissue adhesive material capable of sealing wounds without the use of any crosslinking agent was developed by conjugating thermosensitive hexanoyl glycol chitosan (HGC) with gallic acid (GA). The degree of N -gallylation was manipulated to prepare GA-HGCs with different GA contents. GA-HGCs demonstrated thermosensitive sol-gel transition behavior and formed irreversible hydrogels upon natural oxidation of the pyrogallol moieties in GA, possibly leading to GA-HGC crosslinks through intra/intermolecular hydrogen bonding and chemical bonds. The GA-HGC hydrogels exhibited self-healing properties, high compressive strength, strong tissue adhesive strength and biodegradability that were adjustable according to the GA content. GA-HGCs also presented excellent biocompatibility and wound healing effects. The results of in vivo wound healing efficacy studies on GA-HGC hydrogels indicated that they significantly promote wound closure and tissue regeneration by upregulating growth factors and recruiting fibroblasts compared to the untreated control group.